Evaluating the Evidence for Midline Catheter Use in the Newborn Intensive Care Unit. Issue 6 (November 2015) - Romesberg, Tricia L.
Abstract : When deciding which vascular access devices (VADs) are appropriate for patients in newborn intensive care units (NICUs), clinical providers may have difficulty reaching consensus because of a lack of evidence-based recommendations. The aim of this literature review is to evaluate current research and practice pertaining to midline catheter (MC) use in NICU patients. Discussion of the literature review includes information pertaining to the historical perspective of MC use, devices currently in use, common sites for placement, average dwell times, associated costs, and acceptable fluids and medications for infusion through MCs. Conclusive findings suggest that MCs are not an appropriate VAD for NICU patients because of insufficient high-level evidence demonstrating safety and efficacy. Randomized controlled trials are needed to evaluate current MC practice in the NICU and the rates of infection and extravasation associated with their use.